On the vatiation method in theory of diluted binary melt solidification - Kanischev, V.N.; Barannik, S.V. (Functional Materials, 2006)
It is shown that the differential problem of bidimentional diffusion of impurity particles in a melt being crystallized at a constant speed could be reduced to variation one by selecting an appropriate integral functional. The use of functional so obtained for stability analysis of the flat crystallization fron is exemplified.